2023
DOI: 10.1002/jhm.13193
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to initiate buprenorphine and methadone for opioid use disorder treatment with postdischarge treatment linkage

Susan L. Calcaterra,
Steven Lockhart,
Crystal Natvig
et al.

Abstract: BackgroundHospitals are an essential site of care for people with opioid use disorder (OUD). Buprenorphine and methadone are underutilized in the hospital.ObjectivesCharacterize barriers to in‐hospital buprenorphine or methadone initiation to inform implementation strategies to increase OUD treatment provision.Design, Settings, and ParticipantsSurvey of hospital‐based clinicians' perceptions of OUD treatment from 12 hospitals conducted between June 2022 and August 2022.MeasuresSurvey questions were grouped int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These findings build on previous qualitative work among hospital providers focusing on OUD specifically or substance use more broa dly. 13,15,27,[32][33][34] We also found that the specific substances involved in "polysubstance use" were rarely differentiated, likely limiting providers' ability to develop effective, substance-specific treatment plans in the hospital. 35,36 Stigmatizing views and behaviors toward people with OUD are a well-documented barrier to accessing treatment.…”
Section: Discussionmentioning
confidence: 95%
“…These findings build on previous qualitative work among hospital providers focusing on OUD specifically or substance use more broa dly. 13,15,27,[32][33][34] We also found that the specific substances involved in "polysubstance use" were rarely differentiated, likely limiting providers' ability to develop effective, substance-specific treatment plans in the hospital. 35,36 Stigmatizing views and behaviors toward people with OUD are a well-documented barrier to accessing treatment.…”
Section: Discussionmentioning
confidence: 95%
“… 9 , 10 , 11 There may also be reasons why patients do not want to start MOUD even when it is recommended, such as fear of precipitated withdrawal from buprenorphine 36 ; recent opioid use, which would preclude naltrexone use; or when the patient is not yet ready for OUD treatment. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Medication is only one consideration; hospitals that use other techniques, such as bridge clinics to facilitate ongoing outpatient treatment, substance navigators and/or peer recovery coaches, and dedicated addiction consultation teams, may have more success linking patients to ongoing treatment and encouraging patients to start MOUD . There may also be reasons why patients do not want to start MOUD even when it is recommended, such as fear of precipitated withdrawal from buprenorphine; recent opioid use, which would preclude naltrexone use; or when the patient is not yet ready for OUD treatment …”
Section: Discussionmentioning
confidence: 99%